Spornost EPL in drugih indeksov fleksibilnosti zaposlovanja - prezrti delovnopravni vidiki - Kresal Šoltes, Katarina (Delavci in delodajalci, 2012)
The article criticizes some methods of an economic measure of employment protection legislation regarding its impact on the incremental cost to the employer of hiring and firing workers. EPL and other indices of flexible employment are increasingly used as bases for a decision-making in employment and economic policy at OECD, World Bank and EU level, as well as in Slovenia. The key question is, what is their role regarding the improvement of working conditions and social rights as human rights and whether they respect internationally and constitutionally recognized labour standards.
Keywords: delodajalci; delovno pravo; fleksibilnost; socialna varnost; stroški; zaposleni; zaposlovanje